Cooperation in the law of transboundary water resources - Leb, Christina (Cambridge studies in international and comparati)
"Climate change, population growth and the increasing demand for water are all capable of leading to disputes over transboundary water systems. Dealing with these challenges will require the enhancing of adaptive capacity, the improving of the quality of water-resources management and a reduction in the risk of conflict between riparian states. Such changes can only be brought about through significant international cooperation. Christina Leb's analysis of the duty to cooperate and the related rights and obligations highlights the interlinkages between this duty and the principles of equitable and reasonable utilisation and the prevention of transboundary harm. In doing so, she considers the law applicable to both international watercourses and transboundary aquifers, and explores the complementarities and interaction between the rules of international water law and the related obligations of climate change and human rights law"